Design and Implementation of a Centralized University Result Processing and Transcript System: Case study of University of Ibadan - Osunade, Oluwaseyitanfunmi; Ayinla, Isaiah B.; Aduroja, Olalekan O. (International Journal of Computing Sciences Research; Vol 2 No 3 (2018): Vol 2, No 3, 2019)
Purpose – Result processing and Transcript generation are academic and administrative asks which universities are engaged in on a regular basis. Results inform students of their academic progress while transcript is a record of a student's academic performance. In most tertiary institutions the two tasks are handled separately with manual operations linking the two tasks. The manual operations and interconnections lead to errors in calculations and delay the production of results or transcript. The delay has caused many students or graduates to lose opportunities.  Method – In this work, a combined and centralized result processing and transcript generation system was developed for a tertiary institution. The implementation was done using a Faculty as pilot study before extending to other faculties. Findings – The output shows the results were calculated correctly, graduation parameters applied correctly and reports such as transcript easily generated from the web-based application. Conclusions – The developed transcript and result processing system is functional and operational at the University of Ibadan. It has been used for over 4 academic sessions. The system is compatible with all Nigeria Universities Commission (NUC) regulations. The cooperative result processing technique that ensures results are provided for all registered students and documented permission for result changes are some of the features that users have appreciated. Recommendations – Tertiary institutions in Nigeria are encouraged to customize the developed system to eliminate repetition. Additional security mechanisms such as biometrics may be added as another layer. The system may be hosted in the cloud if there is adequate technical support. Practical Implications – This implies that student academic records are stored digitally and requests for reports such as transcripts and statement of results are efficiently produced. The need for result requests for individual student is over as all results for registered students must be submitted for computation as at when due. Manipulation of results is eliminated due to the multi-layered security built into the operation of the system.